The Effect of Progressive Muscle Relaxation Techniques on Blood Glucose Levels in Elderly With Type 2 Diabetes Mellitus - Aulia Chasana, Trisna; Diah Jerita Eka Sari; Fauzia Zuhroh, Diah; Widiharti , Widiharti (Fundamental and Management Nursing Journal, 2023)
Introduction: The International Diabetes Federation revealed that Indonesia is currently ranked sixth worldwide for deaths from diabetes in 2021. In addition to pharmacological therapy, managing type 2 diabetes mellitus can use non-pharmacological therapies, such as progressive muscle relaxation therapy. This study aimed to analyze the effect of progressive muscle relaxation therapy on blood glucose levels in older people with type 2 diabetes mellitus. Method: This study used a quantitative method with a quasi-experimental approach, pre-test, and post-test with a control group. Sampling technique random sampling of 70 elderly. Instruments: observation sheet of blood glucose levels and PMR SOP. Data analysis using the T-Test. Results: The average blood glucose level before the intervention was 211.7 mg/dl and 183.74 mg/dl after the intervention. In the intervention group, there was an effect with p-value = 0.036 (p-value <0.05). Post-intervention and post-control, there was no difference with a value of 0.074 (p> 0.05), meaning there is no difference. Conclusions: Progressive muscle relaxation affects blood glucose levels in the elderly with type 2 diabetes mellitus at the elderly Posyandu, Singosari Village.